Anatomic and histologic analysis of paca larynx (Cuniculus paca, Linnaeus 1766) - Ruaro, M. A. [UNESP]; Machado, M. R. F. [UNESP]; Garcia, D. O.; Oliveira, A. R.; Dias, F. G. G.; Gomes, S. P.; Leal, L. M.; Sasahara, T. H. C. (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2021)
Paca (Cuniculus paca) has encouraged research as an experimental model both in the human medicine and veterinary, as well as the economic exploitation of its meat cuts, which favored its zootechnical use. There are no anatomical, microscopic descriptions and measurements of the larynx in this rodent. Eight pacas were dissected from the wild animal's sector of the Faculty of Agricultural and Veterinary Sciences of the University of the State of Sao Paulo. The larynx was observed located in the ventral region of the neck, ventral to the esophagus, connecting the pharynx to the trachea, with cylindrical and irregular shape. Laryngeal cartilages (epiglottic, thyroid, cricoid and arytenoid) are interconnected and have different shapes. Thyroid showed greater length and width, compared to the others. Laryngeal cartilages were submitted to histological processing and stained with hematoxylin-eosin and Masson's trichrome. The epiglottic cartilage was stained with toluidine blue. Laryngeal cartilages thyroid, cricoid and the lower portion of the arytenoids are of hyaline origin and, in contrast, the epiglottis and the upper portion of the arytenoids are elastic. This latter cartilage demonstrated taste buds. The results will be able to auxiliate in veterinary care and as well as the conservation programs for this rodent.
Keywords: laryngeal cartilages; morphology; wild rodent; respiratory system